Serum Vitamin D3 level in spontaneous abortion cases in comparison to ongoing viable pregnancies: A case–control study in a tertiary medical college - Chaitali Sengupta; Sengupta , Ritankar; Datta , Dibyendu; Ghosh, Santanu; Naskar, Tapan Kumar (Asian Journal of Medical Sciences, 2024)
Background: The immunoregulatory functions of Vitamin D3 play a vital role in the maintenance of normal pregnancy. Several studies have reported the association of low serum Vitamin D3 levels with spontaneous abortion. Aims and Objectives: The purpose of the study was to determine the association between serum Vitamin D3 level and spontaneous abortion cases in a tertiary medical college. Materials and Methods: The case–control study was conducted at the Department of Gynecology and Obstetrics, Medical College, Kolkata. The study population included 50 women with spontaneous abortion (cases) and 50 women with viable pregnancy beyond 20 weeks of gestation (controls). The cases and controls were matched with respect to age, socioeconomic status, and laboratory parameters. Investigations performed for both groups were ultrasonography for confirmation of abortion and viable pregnancy, serum Vitamin D3, and other biochemical markers. Data were compared between cases and controls using the Chi-square test and unpaired “t” test along with the calculation of odds ratios (OR). Results: About 24% of cases and 10% of controls belonged to Vitamin D3 deficient category. The difference was statistically significant (P=0.009, d.f.=2) (OR: 2.84, 95% confidence intervals [CI]: 0.92–8.80). Bleeding PV was present in 50% of cases and 4% of controls (P=0.0001, d.f.=1) (OR: 24.00, 95% CI: 5.25–109.65). Abdominal pain was complained by 46% of cases and 10% of controls (P=0.0001, d.f.=1) (OR: 7.67, 95% CI: 2.61–22.54). Conclusion: Vitamin D3 deficiency was present more in spontaneous abortion cases in comparison to viable pregnancies. Routine daily supplementation of vitamin D3 during the first trimester of pregnancy should be incorporated into the ongoing national program. Training of health workers to educate pregnant women and their family members regarding the importance of vitamin D3 is the need of the hour.